The role of membrane transporters (NHE-1 and AE-2) in secondary bone healing of tibia-fractured Sprague-Dawley rats - Handool, Kareem Obayes (2017)
Injuries emerging from orthopedic cases are increasingly becoming one of the major areas of attention in medicine. The development of bone has two major pathways, namely intramembranous bone formation and endochondral bone formation. Chondrocyte swelling describes the process emerging from the net movement of water into the cell which relies primarily on an osmotic gradient. It is likely that there is an important role of transporters which regulate the movement of Na+ and anions (e.g., HCO3‾) across the cell membrane as these are known to be essential for the control of cell volume and pH in a wide range of cell types. This study hypothesizes that plasma membrane transporters have a role in cellular differentiation and regulation of endochondral ossification for secondary fracture healing. The objectives of this study were to evaluate the modified device to induce fracture for secondary fracture healing in a rat model, to study the different cellular stages of endochondral ossification, to evaluate the role of specific plasma membrane transporters (Na+/H+ and HCO3‾) in secondary fracture healing and to evaluate the effect of EIPA (5-(N-ethyl-N-isopropyl) amiloride and DIDS (4,4'-diisothiocyano-2,2'- stilbenedisulfonic acid) in secondary bone healing by using a rat tibial fracture model. A total of 55 female Sprague-Dawley rats of 8 weeks old were divided into three experiments: normal fracture healing (n=25, control), EIPA (n=15) and DIDS (n=15). Rats were sacrificed at 1, 2, 3, 4 and 6 weeks post-operative and assessed by clinical observation, radiology, histology, immunohistochemistry examination and statistical analysis. The modified device for producing fractures in the rat model is easy, cheap and reproducible, without complications. The result of gross callus area percentage and gross callus index showed significant difference at week 1 compared to the other weeks (P<0.05); only four rats had slight comminution and 21 rats without comminution. A radiographic examination showed clinical union at week 3 in 60% of the rats, and good clinical union (100%) with less callus formation in week 6. Histomorphometric for woven bone, lamellar bone and bone marrow fibrosis percentage area revealed significant differences (P<0.05). Proliferative and hypertrophic chondrocyte zones percentage area showed a significant difference (P<0.05). Immunoperoxidase staining for NHE-1 and AE-2 revealed significant differences (P<0.05) in all weeks compared to week 6. Following treatment with EIPA and DIDS, gross observation showed that the fracture line was clearly visible until week 4, manual fragment movements continued until week 2 and the callus area was smaller than in normal fracture healing. The X-ray callus index with DIDS treatment showed a significant difference (P<0.05). Histomorphometric with EIPA and DIDS treatment showed that the percentage area for woven bone, lamellar bone, periosteal fibrosis and marrow fibrosis revealed a significant difference (P<0.05); besides, the proliferative and hypertrophic chondrocyte zones percentage area showed a significant difference (P<0.05). Immunohistochemistry density reaction for NHE-1 and AE-2 in EIPA and DIDS showed a significant difference (P<0.05), the density reaction started a weak reaction, then declined directly to be absent in week 4 and week 6, whereas in normal fracture healing a strong reaction for NHE-1 started in the first four weeks then declined in week 6; however AE-2 began at a moderate level then increased strongly in weeks 3 and 4 and declined in week 6. The immunohistochemistry result refers to the direct effect of the inhibitors in the NHE-1 and AE-2 chondrocyte transporter proteins. These results suggest that NHE-1 and AE-2 have a role in the endochondral ossification of secondary bone healing. The inhibition of the hypertrophic chondrocyte zone following treatment with EIPA and DIDS, further strengthened the study hypothesis that NHE-1 and AE-2 inhibit fracture healing.